A strategic management plan for Menruz Trucking Services, Inc. - Garcia, Jocelyn S. (Animo Repository, 2008)
The purpose of this Strategic Management paper is to come up with a comprehensive strategic plan for MENRUZ Trucking Services, Inc. The Strategic Plan began with the identification of the industry. The trucking business is under the transportation industry, an enormous industry which encompass everything from bus to commuter-train systems that move people to the container ships that transport goods from port to port all around the globe. After which, the present task environment was analyzed using the Five Forces Model of Competition by Michael Porter. The resulting changes in the present task environment and the effect of the potential changes to the macroenvironment served as the basis for the identified threats and opportunity. The analysis of the external environment also included the industry and competitive analysis using the strategic map. The module also discussed broader societal expectations using the framework of corporate social responsibility. Module three tackled the internal environment. It presented an overview of the company and the result of the financial analysis from year 2002 to 2006. The financial ratios of the company were further compared with that of the transportation industry and its close competitors. Discussed in details was the value chain of the company divided into primary and support activities. The resulting strength and weaknesses identified was based on the value chain and the financial analysis. The personal value of the owners was discussed using the framework for family business. Module four presented the proposed vision statement, the corporate objectives, evaluation of present strategy, the proposed strategy and the competitive advantage. The basis used for the objectives was the vision while the proposed strategy was based on the threats, opportunities, weaknesses, strengths, broader societal expectations and the personal values. It is recommended that the company pursue its present strategy which is to increase the extent to which it seeks the low-cost position operations and distribution through investment in cost-minimizing equipment. This strategy should be implemented alongside the proposed strategy to expand geographic scope in Regions III and IV. Module five presented in detail the objectives and plan for the strategies based on the following functional areas: (i) Marketing, (ii) Operations, (iii) Finance, (iv) Information Management and (v) Human Resources. The functional strategies were based on the strategic plan and the competitive advantage. Module six discussed the analysis of the company's capability to implement the proposed strategy. It is important to note that the company is a family business and is still relatively small. Thus, before the proposed strategy is implemented, the company will have to focus more on improving the structure and systems. Using the 8-SIT framework, the tasks needed to implement the strategy and the person responsible was identified. A letter to the CEO was also attached, and it details how the company will manage the strategic change. Last but not the least is the financial projections for the year 2008 to 2012 which showed the expected results of the operations based on the proposed strategy.